Spectrophotometric determination of nitrite in water samples with 4-(1-methyl-1-mesitylcyclobutane-3-yl)-2-aminothiazole - Ozmen, H; Polat, F; Cukurovali, A (Taylor & Francis Inc, 2006)
A simple, sensitive, and specific spectrophotometric method for the measurement of nitrite in water has been developed and optimum reaction conditions along with other analytical parameters have been evaluated. The azo dye, 4-( 1-methyl-1-mesitylcylobutane-3-yl)-2-(p-N,N-dimethylazobenzene)-1,3-thiazole was synthesized with the reaction of 4-( 1-methyl-1-mesitylcylobutane-3-yl)-2- aminothiazole and N,N-dimethyl aniline in acidic medium. Obtained azo dye has been characterized by infrared ( IR), H-1 nuclear magnetic resonance ( NMR), and microanalysis methods. The dye shows an absorption maximum at 482 nm. The method is optimized for acid concentration, pH, amount of reagents required, time, and interfering species. All the determinations were carried out at this wavelength throughout the work. At an analytical wavelength of 482 nm, Beer's law is obeyed over the concentration range 0.05 to 2.00 mu g nitrite per mL analyte. The molar absorptivity, Sandell's sensitivity, and relative standard deviation are 2.03 x 10(4) L mol(-1) cm(-1) +/- 251.3 ( 95%), 2.28 x 10(-3) mg cm(-2), and 2.74% ( n = 10), respectively. The detection limit of the method is 0.012 mu g ml(-1) of nitrite ion. The method was succesfully applied to the determination of nitrite in tap water and lake water.
Keywords: spectrophotometric method; aminothiazole; azo dye; nitrite; water